Pemberdayaan ekonomi perempuan melalui pengembangan produk keripik batang pisang di Desa Eran Batu - Febrianto; Nadia Eka Patimah; Sy. Fathya Farhana; Musmunandar; Via Meilana; Salman Taha; Djihan Fadhilah; Abdul Assam; Munira; Indah Purwanengsi; Muhammad Nur Maallah (P3HKI - Universitas Muhammadiyah Parepare, 2024)
This community service aims to empower women's economy in Eran Batu Village through product innovation based on local resources. By utilizing banana stems previously considered waste, this activity succeeded in creating a chip product with promising market potential. Through a series of processing training and mentoring, this service has made a significant contribution to increasing women's knowledge, skills, and self-confidence in entrepreneurship. As a result, new products with added value are created, and a strong social network between women is formed. Furthermore, this service has succeeded in changing people's perceptions regarding the economic potential of local resources and encouraging the use of simple technology in the production process. Thus, this service not only has an economic impact but also a social and cultural impact on the people of Eran Batu Village.